The Significant Relationship between A Prostatitis and A High Level of Glycated hemoglobin in Non-Insulin dependent Diabetes Mellitus in AL-Diwaniah Province - kareem, Aqeel; Sabhan, Ali (Journal of Biomedicine and Biochemistry, 2022)
Objectives: The aim of this study was to determine the effect of type 2 diabetes mellitus (DM) on the serum level of prostatespecific antigen.Background: Prostatitis is an inflammation of prostate gland ; several kinds chronic (nonbacterial) prostatitis and sever(chronic) bacterial prostatitis, pelvic pain syndrome. Glycated Hemoglobin A1c (HbA1c) has been widely recognized as a biomarker predictor for the severity of Diabetes Mellitus(DM). Glycated Hemoglobin (HbA1c) is a pivotal biomarker reflecting both fasting and postprandial plasma glucose concentration over the preceding 120 days. Increasing epidemiologic evidence suggests that diabetes and associated hyperglycemia andinsulin resistance significantly increase the risks of BPH and LUTS.Method: A total of 175 blood samples were tested for Glycated hemoglobin with high R.B. Sugar and PSA level.(HbA1c )might have been quantified by (I Chroma 11 and ELISA).Results: One Hundred Seventy Five patients aged( 22 – 70 ± 10 years) with Type 2 DM, were studied who have signs of prostatitis inflammation ,100 under study and 75 control group.Conclusion: A significant association between poor glycemiccontrol and high PSA level of prostatitis among diabetic patientsunderstudy.